Effect of Sodium Lauryl Sulfate on Orthodontic Elastic Latex’s & Non-Latex’s Tensile Strength - Indryasari; Wibowo, Budi; Vidyahayati, Indah Lestari (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Background : Orthodontic elastic is one of the tools used in orthodontic treatment. Based on the type of material, orthodontic elastics are divided into latex & non-latex. Clinically, orthodontic elastic has decreased tensile strength which can be influenced by various factors including salivary pH and the use of toothpaste. The content of SLS in toothpaste can increase the pH of saliva, causing a decrease in tensile strength. Objective: This study aims to analyze the effect of Sodium Lauryl Sulfate on the elastic tensile strength of latex and non-latex orthodontics. Method : This is an experimental laboratory research with post-test only control group design. The research samples consisted of 15 samples of orthodontics elastics latex and 15 samples of orthodontics elastics non-latex of AO brand with diameter ¼ inches. The samples were divided into 3 groups with latex and non-latex variations in each group, the samples was soaked for 24 hours. Tensile strength was measured using Imada Motorized Tensile Test MV 110 .The statistic used one way Anova test. Result : One way Anova test showed that there was no significant difference between the control group, detergent toothpaste group and non-detergent toothpaste group with p = 0,757 (p > 0,05) for latex and p = 0,382 (p > 0,05) for non-latex. Conclusion : Detergent and non-detergent toothpaste did not affect the tensile strength of orthodontic elastic latex and non-latex.